The state of revenues and expenditures of ukrainian civil society institutions as a reflection of the efficiency of the organization of civil society finances - Tkachuk, Iryna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Purpose. The purpose of the article is to investigate the peculiarities of the formation of revenues and expenditures of civil society institutions in Ukraine (in terms of NGOs and political parties) and to highlight them as a reflection of the effectiveness of the organization civil society finances. Design/methodology/approach. The work consists of several stages. Firstly, the author’s understanding of the category "efficiency of civil society finances" is highlighted. It corresponds to the peculiarities of the functioning of civil society institutions in Ukraine and the world. The study itself consists in a step-by-step analysis of the peculiarities of the formation of revenues and expenditures of civil society institutions in Ukraine (in terms of NGOs and political parties) and their interrelation as a reflection of the effectiveness of civil society finances. Findings. The ratio of revenues and expenditures of Ukrainian NGOs and PPs in the study period characterized the state of the professionalism of financial reporting and planning. It is depends on the mechanism of state regulation and supervision of the finances of PPs and of other CSIs. Thus, improving the existing mechanism of state regulation in the field of finance of CSIs can be an important step towards not only improving the efficiency of finances of civil society, but also the transparency of the public sector. Originality/value. The article is an original complex study, the results of which will be useful both for the leaders of individual civil society organizations and for developers of the state strategy for building civil society. Thus, the population, civil society organizations, the state and civil society itself benefit from the study.